Calibration of effective interface friction angle in granular flow impact experiment - Zhao, Binbin; Zhang, Yingtian; Liu, Yi; Kong, Xiaoang; Liu, Chang; Xu, Xiyu; Deng, Yuanjing (Frontiers in Earth Science, 2022)
By using the normal and tangential forces measured in experiments of granular flow impact against a retaining wall, the effective interface friction angle of the wall was calculated in the dynamic phase and the static phase respectively, designated as δec and δes, and both of them are smaller than the interface friction angle measured by laboratory test (δ2). It is found δec shows an increasing trend against inclination angle (β), which is opposite to that of δes; and δec has an underestimation of effective interface friction angle. By comparing the calculated normal forces of static phase and of dynamic phase with the measured values, it is found the lower bound relation between δes/δ2 and β obtained from regression analysis could well calibrate the effective interface friction angle for both the wall and flume base. It is also noted that the increasing trend of δec against β may be explained by the higher proportion of gravity-friction force at lower inclination angle, i.e., the higher proportion of drag force at higher inclination angle.